Sexual Double Standard, Dating Violence Recognition, and Sexual Assertiveness among University Students in South Korea - Yujeong Kim; Eunmi Lee; Haeyoung Lee (Elsevier, 2019)
Purpose: This study aimed to examine the association among sexual double standard, dating violence recognition, and sexual assertiveness among Korean university students. Methods: Using a cross-sectional survey study in January 2018, Korean university students (N = 322, years; 54.3% female) completed structured questionnaires with the double standard scale, dating violence recognition index, and sexual assertiveness index. The relationship among the variables was analyzed with Pearson's correlations and multiple regression analyses. Results: There were significant correlations among sexual double standard, dating violence recognition, and sexual assertiveness. Sexual double standard (β = .12, p = .043) was determined to influence dating violence recognition. In addition, gender (β = .63, p < .001) and sexual double standard (β = .11, p = .015) were determined to influence dating violence recognition; the explanatory power was 43%. Conclusion: These findings will serve as a basis for the development of education programs that help university students to establish appropriate sexual values and enjoy a healthy sex life. Keywords: intimate partner violence, sexual behavior, sexual health, young adult